2021
DOI: 10.1038/s41598-021-03301-z
|View full text |Cite
|
Sign up to set email alerts
|

Estimating and predicting snakebite risk in the Terai region of Nepal through a high-resolution geospatial and One Health approach

Abstract: Most efforts to understand snakebite burden in Nepal have been localized to relatively small areas and focused on humans through epidemiological studies. We present the outcomes of a geospatial analysis of the factors influencing snakebite risk in humans and animals, based on both a national-scale multi-cluster random survey and, environmental, climatic, and socio-economic gridded data for the Terai region of Nepal. The resulting Integrated Nested Laplace Approximation models highlight the importance of povert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…This research study has important implications for snakebite management in Iran. As shown in other studies 13 , 27 30 , 45 , 46 and confirmed in this research HSMs developed based on distribution of medically important venomous snakes can guide public policies for the distribution of antivenom medication and identification of regions with higher snakebite risk to guide mitigation and training measures for vulnerable populations as well as health teams. It should be noted that population density, educational level, income, etc.…”
Section: Discussionsupporting
confidence: 83%
“…This research study has important implications for snakebite management in Iran. As shown in other studies 13 , 27 30 , 45 , 46 and confirmed in this research HSMs developed based on distribution of medically important venomous snakes can guide public policies for the distribution of antivenom medication and identification of regions with higher snakebite risk to guide mitigation and training measures for vulnerable populations as well as health teams. It should be noted that population density, educational level, income, etc.…”
Section: Discussionsupporting
confidence: 83%
“…Ensuring that actors from endemic nations are leading snakebite initiatives might enhance legitimacy and enable inclusion of a wider base of proponents. The use of One Health as a framework for understanding and addressing snakebite might also be considered: it has successfully attracted large multicountry collaborative funding 62 63. The joint action plan of WHO, Food and Agriculture Organization of the United Nations, World Organisation for Animal Health & United Nations Environment Program identifies snakebite as an area of work in 2022–2026 64.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches such as the waterpoint approach may correlate with snake population density, especially in arid and semi-arid regions. There is emerging evidence that distance to water sources may predict the risk of snakebite in some communities [ 45 ].…”
Section: Discussionmentioning
confidence: 99%